2021
DOI: 10.21608/asdj.2021.56107.1005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of The Effect of Diode Laser on Root Canal Disinfection, Canal Cleanliness, Fracture Resistance of Tooth Structure and Bond Strength to Root Canal Dentin An in Vitro Study

Dina Barakat

Abstract: The aim of this study was to assess and investigate the effect of diode laser on root canal disinfection, and root canal cleanliness, as well as its effect on the fracture resistance of tooth structure, and on the bond strength of resin sealer to the root canal wall. Materials and MethodsA total of 160 single rooted teeth were selected, and separated into two experimental groups (n=80), Group A were finally irrigated using 980 nm diode laser. Group B were finally irrigated using NaOCl/EDTA. Samples were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…In this study, the fracture resistance of root was found to be high after diode laser activation. This came in agreement with Quteifan et al (32) and Barakat et al (33) that accredited it to the fact that laser can glaze, melt, and recrystallize dentin, where such molten dentin layer solidifies and close slight transient surface cracking. In the opposite side a study by Ayrancı et al (34) stated that laser decreased the fracture resistance of dentin, this may be attributed to the difference in the study design and methods as the vertical root fracture resistance test was done on apicoected teeth, also they claimed that the decrease of fracture resistance might be due to alteration in structural composition of dentin.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the fracture resistance of root was found to be high after diode laser activation. This came in agreement with Quteifan et al (32) and Barakat et al (33) that accredited it to the fact that laser can glaze, melt, and recrystallize dentin, where such molten dentin layer solidifies and close slight transient surface cracking. In the opposite side a study by Ayrancı et al (34) stated that laser decreased the fracture resistance of dentin, this may be attributed to the difference in the study design and methods as the vertical root fracture resistance test was done on apicoected teeth, also they claimed that the decrease of fracture resistance might be due to alteration in structural composition of dentin.…”
Section: Discussionsupporting
confidence: 88%